Valorization and using of mining waste from Djebel Onk (TEBESSA) for the synthesis of nano-composites - BOUKHALFA Hadil; OUBBICHE Doaa (University of Shahid Hama Lakhdar - El Oued, 2024)
Nanotechnology is a multidisciplinary field, as it combines the knowledge of different disciplines: Chemistry, physics, biology... We conducted a study to evaluate the catalytic activity of nanocomposites found in medicinal plants by utilizing minerals found in varying proportions in mineral residues from the phosphate mining process in the neck mountain mine instead of resorting to synthesized minerals, Therefore, we investigated the properties of peppermint plant and synthesized nanocomposites extracted from peppermint plant extract, the properties of these compounds were studied using UV-Vis, XRD, FTIR and bacterial activity. We concluded that HD-NC is a good catalyst for many reactions, resistant to pollution and has a role in the environment. تكنولوجيا النانو هي مجال متعدد التخصصات، حيث أنها تجمع بين المعرفة تخصصات مختلفة: الكيمياء، الفيزياء، الأحياء... أجرينا دراسة ل تقييم النشاط التحفيزي للمركبات النانوية الموجودة في النباتات الطبية بواسطة الاستفادة من المعادن الموجودة بنسب متفاوتة في المخلفات المعدنية من عملية استخراج الفوسفات في منجم جبل العنق بدلا من اللجوء إليه المعادن المصنعة، لذلك قمنا بدراسة خصائص النعناع المركبات النانوية النباتية والمركبة المستخرجة من مستخلص نبات النعناع، تمت دراسة خواص هذه المركبات باستخدام الأشعة فوق البنفسجية UV-Vis، XRD، FTIR و النشاط البكتيري. لقد استنتجنا أن HD-NC يعد محفزًا جيدًا للعديد من التفاعلات ومقاومًا لها التلوث وله دور في البيئة
Master's theses in chemical engineering
Keywords: mint plant; green synthesis; metal waste; nanocomposites.; نبات النعناع، ​​التخليق الأخضر، النفايات المعدنية، المركبات النانوية.